1887 Ala. Code 93, § 4093 - (:unkn) unknown (My University, 1887)
Prohibited storage of gun powder exceeding fifty pounds within any incorporate city or town. Violators fined not less than one hundred dollars.
Keywords: GUNPOWDER - STORAGE